Unveiling the anatomy of Termination 3 using water and air isotopes in the Dome C ice core, East Antarctica. (1st May 2019) - Bréant, Camille; Landais, Amaëlle; Orsi, Anaïs; Martinerie, Patricia; Extier, Thomas; Prié, Frédéric; Stenni, Barbara; Jouzel, Jean; Masson-Delmotte, Valérie; Leuenberger, Markus
Abstract: Each glacial – interglacial transition of the Quaternary occurs in a different orbital context leading to various timing for the deglaciation and sequence of high vs low latitudes events. Termination 3, 250 kyears before present (ka), is an unusual deglaciation in the context of the last 9 deglaciations recorded in the old EPICA Dome C (EDC) Antarctic ice core: it exhibits a three-phase sequence, two warming phases separated by a small cooling, the last phase suggesting a particularly rapid temperature increase. We present here new high resolution δ 15 N and deuterium excess (d-excess) data from the EDC ice core to provide a detailed temperature change estimate during this termination. Then, we combined the δD and δ 18 O to discuss the relationship between high and low latitude changes through the d-excess. We also provide the high vs low latitude sequence of events over this deglaciation without chronological uncertainty using low latitude ice core proxies. In agreement with previous studies based on speleothem analyses, we show that the first phase of Termination 3 (256–249 ka) is associated with small Heinrich like events linked to changes in ITCZ position, monsoon activity and teleconnections with Antarctica. In a context of minimum Northern Hemisphere insolation, this leads to a rather strong Antarctic warming, as observed in the δ 15 N record in contrast to the relatively small δD increase. The second warming phase occurs during the rise of the Northern hemisphere insolation, with a large Heinrich like event leading to the characteristic Antarctic warming observed in the δ 15 N and δD increase as for the more recent terminations. Highlights: New high resolution δ 15 N and d-excess measurements over Termination 3 provide a quantification of temperature evolution over this period. Three-phase high vs low latitude sequence of events over Termination 3 in a context of enhanced millennial scale variability. Impurity contents does not play a major role on the δ 15 N evolution over deglaciations.